2010
DOI: 10.1158/1078-0432.ccr-09-1978
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Synthetase Immunostaining Correlates with Pathologic Features of Hepatocellular Carcinoma and Better Survival after Radiofrequency Thermal Ablation

Abstract: Purpose: Activation of the wnt pathway identifies a subgroup of hepatocellular carcinomas (HCC) with specific epidemiologic and genetic profiles. Wnt activation is predicted by mutation and/or nuclear translocation of β-catenin and by glutamine synthetase (GS) immunoreactivity. We investigated whether GS staining associates with specific pathologic features of HCC and with survival after radiofrequency thermal ablation.Experimental Design: Monoistitutional retrospective-prospective study in a tertiary hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…21,22 Differences in the clinical outcome of HCCs diagnosed at the same stage in patients with preserved liver function may reflect biological differences of the tumor and cirrhotic liver tissue. 37,38 This study also shows that mortality unrelated to cancer progression has an important impact on the survival of HCC patients, who in Western countries are generally elderly. 3,4,32 In conclusion, our ability to select optimal treatment strategies for patients with cirrhosis with HCCs is currently limited by three factors: (1) unpredictability of tumor progression and de novo carcinogenesis 37,38 ; (2) tumor understaging 14 ; and (3) substantial risk of HCCunrelated death.…”
Section: Discussionmentioning
confidence: 59%
“…21,22 Differences in the clinical outcome of HCCs diagnosed at the same stage in patients with preserved liver function may reflect biological differences of the tumor and cirrhotic liver tissue. 37,38 This study also shows that mortality unrelated to cancer progression has an important impact on the survival of HCC patients, who in Western countries are generally elderly. 3,4,32 In conclusion, our ability to select optimal treatment strategies for patients with cirrhosis with HCCs is currently limited by three factors: (1) unpredictability of tumor progression and de novo carcinogenesis 37,38 ; (2) tumor understaging 14 ; and (3) substantial risk of HCCunrelated death.…”
Section: Discussionmentioning
confidence: 59%
“…35 Some studies have also shown that the downregulation of GLUL, a key enzyme in glutamine synthesis, correlates with a worse prognosis in some tumors. 36,37 Accordingly, our data indicate that when cocultured with fibroblasts under conditions that better mimic the tumor microenvironment, cancer cells display the downregulation of GLUL, suggesting a decreased need for glutamine neogenesis, and increase GLS and GLUD1, two key enzymes in glutamine catabolism. It will be important to evaluate the prognostic value of GLS and GLUL in the different tumor compartments (stromal vs. epithelial), especially as this relates to tumor progression.…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, mechanotransduction-induced YAP signals promote the generation of CAFs, suggesting a complex interplay between tumor mechanics and stromal fibroblasts that contributes to the evolution of key components of the TME (77). In addition, specific genomic profiles of HCC appear to influence the activation of the stromal compartment as demonstrated by lower fibrosis in patients with beta-catenin-mutated HCCs (78, 79). There is increasing evidence from clinical studies that the presence of liver fibrosis, α-SMA-positive myofibroblasts, or activated HSC signatures is associated with a poor prognosis after curative HCC resection, suggesting a key role of the fibrotic TME in promoting HCC progression: In patients with curative HCC resection, a high degree of peritumoral myofibroblast infiltration was associated with a 2.6-fold hazard ratio for overall survival and a 3.3-fold hazard ratio for recurrence-free survival (52).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%